Relationship of Public Value to The Implementation of Stunting Policy in Bengkulu Province - Kanedy, Muhammad Adnan Al Kadly; Achmad Lutfi (Jurnal Administrasi Publik (Public Administration Journal), 2023)
This article aims to explain the policy of implementing stunting in Bengkulu Province which is related to public values. The problem is focused on the condition that Bengkulu is one of the regions that has a fairly high stunting percentage rate in 2022, namely 22 percent where in the context of tackling stunting problems, the Bengkulu Provincial Government seeks to formulate and implement policies or regulations that are in favor of public values. The Provincial Government of Bengkulu has launched various programs in an effort to accelerate the prevention of stunting which includes parenting and assisting mothers and children, eating patterns, and environmental sanitation. In order to approach this problem, references from Timo Meynhard's theory (2020) are used, where the measurement of public values ​​consists of Moral-Ethics, Aesthetic-Hedonistic, Instrumental-Utilitarian, and Socio-Political. The data were collected through interviews, literature studies, documentation studies, some relevant information derived from statutory policies and related reports and were analyzed qualitatively. This study concludes that stunting prevention policies in Bengkulu Province must focus on the context of implementing policies that are synergistic between local governments by emphasizing nutrition, the environment and household sanitation, as well as education related to stunting prevention and treatment which are two-way in nature and are supported by a budget for run the work program.